Keamanan Psikologis dan Kesejahteraan Relasional pada Guru di Lembaga Pendidikan Islam: Menuju Kerangka Perilaku Organisasi Relasional Islam - Dian Mayasari (CV. Eureka Artha Nusantara, 2026)
Psychological well-being in Islamic educational institutions is often examined through individual outcomes such as job satisfaction, motivation, and occupational stress, while the relational conditions through which teachers experience safety, belonging, and mutual support remain comparatively underexplored. This study addresses this gap by examining the relationship between psychological safety and relational well-being among teachers and developing an Islamic Relational Organizational Behavior framework. Employing an integrative conceptual approach, the study synthesizes scholarship on psychological safety, relational well-being, organizational behavior, teacher well-being, and Islamic ethical principles to identify their conceptual intersections and explanatory mechanisms. The analysis indicates that psychological safety functions not merely as an individual psychological state but as a relational condition shaped by interpersonal trust, organizational justice, participatory communication, and leadership practices. Within Islamic educational institutions, these relational processes can be ethically grounded in 'adl (justice), ihsan (benevolence and excellence), amanah (moral responsibility), shura (deliberative participation), and ukhuwah (relational solidarity). The resulting framework positions relational well-being as an organizational outcome emerging from psychologically safe and ethically structured relationships, which subsequently facilitates constructive organizational behaviors, including mutual support, collaborative engagement, teacher voice, and organizational learning. The study contributes theoretically by extending organizational behavior scholarship beyond individual-centered well-being toward an Islamic relational perspective and offers a framework for rethinking teacher well-being, organizational culture, and human relations in Islamic educational institutions.